Contra ( i,j ) -Sc- Continuous Function - Aziz, Hardi N. (Sulaimani Journal for Pure and Applied Sciences, 2015)
In this paper, a new type of continuity in Bitopological spaces has been introduced, namely Contra ( ) continuity. Also, the relationship between this type of continuity and several other known type of continuity has been dealt with.
Keywords: i; j Sc open set; Contra semi continuous; Contra continuous